Silver Nanoparticles as optical sensors - Wang, Chien Chun (2010)
Silver nanoparticles as optical sensors. Chien C. Wang, Marta O. Luconi, Adriana N. Masi, Liliana P. Fernández Silver nanoparticles (AgNPs) have attracted great attention due to their potential applications in analytical and bioanalytical sensing, beside others. This is based on their unique optical properties derived from the excitation of surface plasmon resonance (SPR). As a secondary process, it may be also accompanied by a strong scattering, depending of the particle sizes. High sensitivity of the spectral response of the SPR and scattering band have been used in determinations of organic and inorganic analyte traces and the number of related papers is in continuous increase. The present chapter has the objective to offer a recopilation of recent advances in analytical and bioanalytical applications of silver nanoparticles associated to the optical phenomena. Particular attention will be provided to new analytical spectral techniques, taking into account their advantages respect to sensitiveness and selectiveness, as follow: a- Surface-enhanced Raman scattering (SERS); b- Surface-enhanced resonance Raman scattering (SERRS); c- Resonance Rayleigh scattering (RRS); d- Second order scattering peak (SOS). The success of new applications of silver nanoparticles depends on improvement in the understanding of the properties of SPR. Systematic study must be assumed in order to offer new developments to extend the analytical applications field of silver nanoparticles.